(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Previously, curcumin analogue, 2, 6-bis (2, 5-dimethoxybenzylidene) cyclohexanone (BDMC33) with high anti-inflammatory activity was chemically synthesized in our laboratory to enhance the biological activity of curcumin. In this study, the toxicity and permeability activities of 2,6-bis(2,5-dimethoxybenzy-lidene)cyclohexanone (BDMC33) in Caco-2 cells was investigated. Toxicity effects using MTT assay and apparent permeability coefficient (Papp), uptake (UR) and efflux (ER) ratios, and mass balance of BDMC33 after permeation in Caco-2 cells for 180 min were evaluated in apical (A) to basolateral (B) and basolateral (B) to apical (A) directions. The similar analyses on 3-(2-fluoro-benzylidene)-5-(2-fluorocyclohexylmethylene)-piperidin-4-one; (EF-24) (check control) were also conducted. The 24 hr LC50 value for BDMC33 and EF-24 on Caco-2 cells were both 50 µM. The Papp value in A→B direction was 3.37 ± 0.47 cm/s (BDMC33) and 2.47 ± 0.15 cm/s (EF-24). Whereas in B→A direction, it was 1.9 ± 0.36 cm/s (BDMC33) and 1.8 ± 0.15 cm/s (EF-24) upon 120 min incubation. The UR and ER ratios calculated were 1.77% and 0.56%, respectively, and the mass balance calculated were 41-44% (BDMC33) and 31-34% (EF-24) in A→B and B→A direction. This study has suggested BDMC33 to be more absorbable than EF-24 in Caco-2 cells. Therefore, BDMC33 could be a leading feature, the anti-inflammatory agent, as it biological activities would be expected outside the intestine.